Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 5 Polynomials and Polynomial Functions - 5.9 Write Polynomial Functions and Models - 5.9 Exercises - Skill Practice - Page 397: 10



Work Step by Step

We need to plug in $x=0$ and $y=3$ in order to get the correct answer. Here, we have $y=a(x+3)(x-3)(x+1)$ $3=a(0+3)(0-3)(0+1)$ or, $3=-9a$ This gives: $a=-\dfrac{1}{3}$ Thus, we have $y=-\dfrac{1}{3}(x+3)(x-3)(x+1)$ Thus, the answer is $B$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.